Preventing Early Marriage through Family-Based Islamic Counselling: A Community Intervention Model for Muslim Adolescents - Faqihudin Faqihudin (Sekolah Tinggi Agama Islam Kuningan, 2025)
Early marriage remains a critical global concern, with approximately 12 million girls married annually before age 18, particularly affecting Muslim-majority communities where cultural norms intersect with religious interpretations. Despite international commitments under SDG 5.3, limited culturally grounded interventions exist that address both spiritual dimensions and family decision-making structures central to Muslim societies. This study aimed to develop and evaluate a family-based Islamic counseling model as a culturally resonant intervention to prevent early marriage among Muslim adolescents, specifically examining its effectiveness in transforming family perceptions, parent-child communication patterns, and religious value interpretations. Using a qualitative descriptive design, this research was conducted in two rural and two semi-urban Muslim communities in Central Java, Indonesia, involving 45 participants (15 families, 15 adolescents aged 13-19, 10 community counselors, and 5 religious leaders) over six months (January-June 2024). Data were collected through in-depth interviews, non-participant observations of counseling sessions, and document analysis, then analyzed using Braun and Clarke's thematic analysis framework. Results revealed that Islamic counseling effectively reshaped families' understanding of marriage readiness by clarifying Islamic concepts of rushd (maturity), maslahah (welfare), and ridha (consent). Parent-child communication improved significantly through empathetic dialogue, and families demonstrated more cautious decision-making grounded in holistic Islamic principles rather than cultural assumptions. The intervention model achieved strong community acceptance when integrated into existing religious institutions. This study contributes a replicable, faith-sensitive counseling framework that aligns with both Islamic ethics and developmental psychology, offering practical strategies for policymakers, religious leaders, and educators to strengthen adolescent protection in Muslim-majority contexts.